Assessment of the intermediate care unit triage system - Plate, Joost D J (Trauma Surg Acute Care Open, 2018)
BACKGROUND: An important critique with respect to the utilization of intermediate care units (IMCU) is that they potentially admit patients who would otherwise be cared for on the regular ward. This would lead to an undesired waste of critical care resources. This article aims to (1) describe the caseload at the IMCU and (2) to assess the triage system at the IMCU to determine potentially unnecessary admissions. METHODS: This cohort study included all admissions at the mixed-surgical IMCU from 2001 to 2015. The Therapeutic Intervention Scoring System-28 (TISS-28) was prospectively collected for all admissions to describe the caseload at the IMCU and to identify medical criteria for admission. These were combined with logistical criteria to assess the IMCU triage system. RESULTS: A total of 8816 admissions were included in the study. The average TISS-28 was 20.19 (95% CI 18.05 to 22.33), corresponding with 3.57 (95% CI 3.19 to 3.94) hours of direct patient-related work per patient per nursing shift. Over time, this increased by an average of 0.27 points/year (p<0.001). Of all admissions, 6539 (74.2%) were medically considered to be justly admitted, and 7093 (80.4%) were logistically considered to be justly admitted. With these criteria combined, a total of 8324 (94.4%) were correctly admitted. DISCUSSION: Most admissions to the IMCU are medically and/or logistically necessary, as the majority of admitted patients demand a higher level of nursing care than available on the general ward. Continuous triage is thereby essential. These findings support further utilization of the IMCU in our current healthcare system and has important implications for IMCU-related management decisions. LEVEL OF EVIDENCE: Level VI.